2002
DOI: 10.1097/00126334-200209010-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Mycophenolate Mofetil to Antiretroviral Therapy Including Abacavir Is Associated With Depletion of Intracellular Deoxyguanosine Triphosphate and a Decrease in Plasma HIV-1 RNA

Abstract: Mycophenolic acid (MPA) enhances the in vitro activity of abacavir (ABC) and other nucleoside analog reverse transcriptase inhibitors (NRTIs) against sensitive and NRTI-resistant HIV-1. This may occur via depletion of intracellular deoxyguanosine triphosphate (dGTP). Mycophenolate mofetil (MMF) 500 mg twice daily was added as a single agent to the antiretroviral regimens of five patients failing maximal available therapy. Therapy included ABC, and in most cases didanosine (DDI) and tenofovir (TDF). At entry, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…However, Fasola et al (33) showed that manifestations of hepatitis C disease recurrence after steroidresistant allograft rejection following orthotopic liver transplantation seems to be less severe in patients who use mycophenolate. Mycophenolate has also been used as adjunctive therapy in the treatment of HIV infection (34,35). However, some of the benefit of mycophenolate use may also be due to lowered rates of acute rejection after transplantation (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, Fasola et al (33) showed that manifestations of hepatitis C disease recurrence after steroidresistant allograft rejection following orthotopic liver transplantation seems to be less severe in patients who use mycophenolate. Mycophenolate has also been used as adjunctive therapy in the treatment of HIV infection (34,35). However, some of the benefit of mycophenolate use may also be due to lowered rates of acute rejection after transplantation (36).…”
Section: Discussionmentioning
confidence: 99%
“…MPA has been shown to increase the in vitro anti-HIV activity of ABC when used in combination (21). Several pilot clinical studies have been conducted to evaluate the effect of MPA (given as the prodrug MMF) in combination with HAART (8,9,22). Overall, therapy with MMF resulted in a transient decrease in HIV viral load in the majority of patients.…”
mentioning
confidence: 99%
“…Potential clinical implications need to be evaluated in the future, including assessment of the analog/dNTP ratio over time, which influences the pharmacological efficacy of TDF/FTC (3,4,12).…”
Section: Discussionmentioning
confidence: 99%
“…Participants' age, weight, sex, race, and body mass index (BMI) were recorded upon enrollment in the study. Peripheral blood mononuclear cell (PBMC) samples were taken at baseline and at 8 h postdose on days 1,3,7,20,30, and 60 in all participants. The HIV-negative group had two additional visits on days 35 and 45 during the washout period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation